2020
DOI: 10.1523/jneurosci.0127-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

α3* Nicotinic Acetylcholine Receptors in the Habenula-Interpeduncular Nucleus Circuit Regulate Nicotine Intake

Abstract: Allelic variation in CHRNA3, the gene encoding the a3 nicotinic acetylcholine receptor (nAChR) subunit, increases vulnerability to tobacco dependence and smoking-related diseases, but little is known about the role for a3-containing (a3p) nAChRs in regulating the addiction-related behavioral or physiological actions of nicotine. a3p nAChRs are densely expressed by medial habenula (mHb) neurons, which project almost exclusively to the interpeduncular nucleus (IPn) and are known to regulate nicotine avoidance be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 40 publications
5
45
0
Order By: Relevance
“…More recently, targeted knock-down of a3 nAChR subunit in either MHb or IPN was shown to produce similar increases in nicotine intake [24]. Global overexpression of β4 nAChR subunit led to increased nicotine aversion, an effect reversed by selective expression of a5 nAChR subunit in MHb [21].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…More recently, targeted knock-down of a3 nAChR subunit in either MHb or IPN was shown to produce similar increases in nicotine intake [24]. Global overexpression of β4 nAChR subunit led to increased nicotine aversion, an effect reversed by selective expression of a5 nAChR subunit in MHb [21].…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, overexpression of b4 nAChR subunit leads to enhanced MHb activity and a strong aversive response to nicotine, which can be abolished by disruption of the a5 nAChR subunit in MHb [21]. More recently, it has been shown that knockdown of the a3 nAChR subunit in either the MHb or IPN increases nicotine intake in rats [24]. These data together suggest that nAChRs containing the a5, a3, and b4 subunits mediate aversive signaling in the MHb-IPN.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The habenula has high levels of nAChR expression and one of the brain regions with the greatest (>30% of total) levels of non‐α4β2 nAChRs in the brain (Whiteaker, Jimenez, et al, 2000). These non‐α4β2 nAChRs, notably α3*, α5*, and β4* nAChRs, are involved with withdrawal symptoms and nicotine intake, and are highly expressed in the habenula (Elayouby et al, 2021; Velasquez et al, 2014). Several studies have characterized the functional implications of reduced nAChR signaling from the habenula.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, mice with overexpression of the β4 nAChR gene exhibit a strong aversion to nicotine (Frahm et al, 2011). Finally, knockdown of the α3 nAChR subunit in the MHb or IPN increases nicotine intake at higher doses, a behavioral effect also found with the infusion of the α3β4 antagonist, a-conotoxin AuIB, into the IPN (Elayouby et al, 2021). Interestingly, the α3β4-containing nAChR has further been implicated in the physical signs of nicotine withdrawal (Jackson et al, 2013), which may involve altered GABAergic signaling in the IPN (Zhao-Shea et al, 2013).…”
Section: Nicotine's Actions On Brain Circuits Underlying Addictionmentioning
confidence: 96%